Pengaruh Limbah Beton Sebagai Agregat Kasar Pada Campuran AC-BC dengan LGA 50/30 - Pristyawati, Tantin; Nugraha, Diky Candra (Jurnal Ilmiah Rekayasa Sipil, 2024)
Road infrastructure has a function as one of the supporters of the development of an area. The Road infrastructure still used today is a flexible pavement composed of a mixture of asphalt and aggregate, which is heated and then compacted. Asphalt serves as a binder in the flexible pavement to maintain density and resist the weathering of aggregates caused by weather. It is an innovative additive used in concrete waste to replace rough aggregates. Adding LGA B50/30 in a base mixture is expected to be an alternative to improving the quality of the base mix and supporting the government in the use of domestic products. The study aims to determine how marshall is characterized if concrete waste is used in the AC-BC Ashburton mix as a substitute for rough aggregates and whether it meets the requirements of the Binna Marga Specification. The study was conducted experimentally with marshal characteristic parameters density, VIM (Void In Mix), VMA (Void In Mineral Aggregate), VFA (Void Filled with Asphalt), stability, and Marshall Quotient. (MQ). The Optimum Asphalt Rate used is 6.5%. The result is the density decreases with the addition of concrete waste levels, with the highest value at the 30% concrete waste level of 2,408 gr/cc. The increase in the VIM value with the addition of the concrete residue level has a higher value at a rate of 70% or 4.66%. The highest MQ is at a 50% concrete waste rate of 334.04 kg/mm. The study results show that waste concrete innovation materials can be used in Asbuton AC-BC mixtures with levels not exceeding 60%. Based on this research, concrete waste can be an alternative to natural aggregate substitutes.